Latin america and china’s belt and road initiative: challenges and proposals from a Latin American perspective - Fernández, Víctor Ramiro (2023)
Despite the divergent perspectives that address the presence of China in the Global South through the Belt and Road Initiative, scarce approaches identify how Latin America could face that challenge to reverse its historical dependency and promote economic development. We address this question by recovering and updating structuralist, dependentist, and autonomist contributions developed in Latin America combined with an arrighiean version of the world system. We compare the Latin American and Chinese trajectories regarding regional integration, productive and technological constitutions, spatial asymmetries, and state capacities. Finally, we propose how to forge a relationship with China that enhances Latin American autonomy.